Determinants of retention in Negeri Roadstone Sendirian Berhad / Nurul Shafikah Hussien - Hussien, Nurul Shafikah (2011)
This research been done to analyze the determinants of employee retention in Negeri Roadstone Sdn Bhd. It begins with the background of the company, discussing about the historical of Negeri Roadstone Sdn Bhd and overview of retention. Then, followed by the research problem that leads to the research objective. Next, the significance of study discussed so that will clarify some ideas towards the research. Several research question also been determined to generate the study. As guidance for future generation, these researches will help to create better understanding towards Human Resource practitioner, management and other organization, lead to the factors that can boost retention in their field of work.